Doha Development Agenda and Aid for Trade. (Policy Papers; Policy Paper ;, 2006)
This paper summarizes recent developments in the Doha Round negotiations, and aid for trade. As requested by the Development Committee last September, it reviews existing mechanisms for cross-country and regional aid for trade needs. It proposes possible options to overcome the coordination and capacity problems affecting regional cooperation.